Development and Evaluation of Module on Earth and Space - Jomar M Urbano (ASEAN Multidisciplinary Research Journal, 2019)
This study entitled “Development and Evaluation of Module on Earth and Space” centered on the development of a module that provides activities and lessons for students to learn and eventually improve their academic performance in Science. Following the protocol of utilizing a learning material, the Module was evaluated using a set questionnaire. Based on the collected, computed, and tabulated data, the Module was described by the teacher respondents to have specific, measurable, attainable, realistic, and time-bound and relevant learning objectives. The module has simple, appropriate and enjoyable illustrations which are logically and properly sequenced. It also provides procedures and contains available materials prescribed in the activities. Furthermore, the Module provides the learners to think logically and critically, all of which are relevant requirements for students to learn and eventually improve their academic performance. The teacher respondents strongly agreed that the evaluation portion of the module provides effective measurement in determining the students understanding as it reflects behavioral activities which are highly appropriate to the learners’ mental development and provides rubrics to evaluate the students objectively; thus, preparing the learners to become independent and confident in learning Science.